2018
DOI: 10.5535/arm.2018.42.4.569
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Walking Ability and Monthly Care Costs in Elderly Patients After Surgical Treatments for Hip Fractures

Abstract: ObjectiveTo validate the relationship between residual walking ability and monthly care cost as well as long-term care insurance (LTCI) certification level in elderly patients after surgical treatment for hip fractures in Japan.MethodsElderly patients aged >75 years who underwent surgical treatment for hip fractures in our hospital were included. The preand post-surgical (6-month) walking ability and LTCI certification and the presence or absence of dementia was determined from medical records and questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…30 Furthermore, monthly care costs were correlated with walking ability in elderly patients after surgical treatments for hip fractures. 31 In Taiwan, Lin and Lu 32 reported that the families of geriatric patients with hip fracture experienced a high care burden within 1 month of hip surgery, and up to 77.6% of the families needed help with care tasks. 32 However, clinical reports on changes in care demands in the long term are lacking, and long-term functional loss may be inevitable among geriatric patients with hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…30 Furthermore, monthly care costs were correlated with walking ability in elderly patients after surgical treatments for hip fractures. 31 In Taiwan, Lin and Lu 32 reported that the families of geriatric patients with hip fracture experienced a high care burden within 1 month of hip surgery, and up to 77.6% of the families needed help with care tasks. 32 However, clinical reports on changes in care demands in the long term are lacking, and long-term functional loss may be inevitable among geriatric patients with hip fracture.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, nearly 50% lose their walking independence, and those with a rapid decline in gait speed would suffer from an increased risk of disability by 77% and mortality by 90% 7 9 . Additionally, losing walking independence (LWI) led to increased care costs and a greater burden on the long-term care insurance system 10 . More efforts are urgently needed to improve the walking outcomes of older patients with hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the improvement of daily living activities is crucial for the outcomes of hip fractures, as individuals with decreased functional Status have an increased risk of disability and mortality [ 14 16 ].In addition, loss of mobility can lead to increased nursing costs and greater burden on the long-term care insurance system [ 17 ].…”
Section: Introductionmentioning
confidence: 99%